Systemic Lupus Erythematosus Patients With Related Organic Damage Are at High Risk of Hypothyroidism - Ni, Jiajia; Li, Jingyi; Wang, Yuyao; Guan, Liying; Lin, Haiyan; Zhang, Li; Zhang, Haiqing (Frontiers in Endocrinology, 2022)
Purpose: The aim of this study included determining the prevalence of hypothyroidism in patients with systemic lupus erythematosus (SLE), clarifying the clinical characteristics of SLE patients with hypothyroidism, and identifying the relationship between hypothyroidism and SLE-related organic damage. Another purpose was to analyze the relationship between SLE and thyroid autoantibody. We also intended to discuss the pathogenesis of hypothyroidism in SLE patients, which would provide clues for further investigation. Methods: This study recruited 856 SLE patients and 856 age- and sex-matched healthy population and compared the prevalence of hypothyroidism between the cases and controls. Univariate and multivariate logistic analyses were applied to identify risk factors for hypothyroidism in SLE patients. Results: SLE patients had higher prevalence of clinical hypothyroidism (9.10%) and TgAb+TPOAb- (10.40%) than controls. The prevalence of hypothyroidism was the highest in SLE patients aged 16-26 years (18.9%) and decreased with age. The prevalence of autoimmune hypothyroidism in SLE group was higher than that in the control group (64.4% vs. 51.5%, P=0.042), which was mainly due to TgAb; the prevalence of non-autoimmune hypothyroidism in SLE group was also significantly higher than that in the control group (67.3% vs. 47.8%, P<0.001). Based on multivariate analysis, the use of glucocorticoids/immunosuppressants, liver abnormality, lupus nephritis (LN), and cardiac insufficiency were independently associated with hypothyroidism in SLE patients. Conclusion: The prevalence of hypothyroidism in SLE patients was higher than that in controls and decreased with age. The results suggested that young SLE patients combined with LN, liver abnormality and cardiac insufficiency were at higher risk of hypothyroidism. According to the results of this study, we speculated that SLE might have impact on thyroid, and SLE might be one of the causes of hypothyroidism.